Prompt Engineering in Higher Education: Perceptions, Practices, and Pedagogical Potentials - Akyıldız, Seeil Tumen (IGI Global Scientific Publishing, 2025)
This study examines how university instructors in Eastern Türkiye perceive and use prompt engineering in higher education. Using an interpretivist/constructivist stance, a generic qualitative design and reflexive thematic analysis were employed. Fifteen instructors from five state universities were intervieweduntilsaturation. Four perception areas emerged: a practical, instruction-focused view; recognition of student-centered potential; challenges from lackoftraining; andvarying motivation. In practice, prompts supported material design, assessment, and critical thinking, while research use was limited to idea generation, summaries, and tool drafting. Ethical concerns were stronger among senior staff, while early-career academics were more confident. The study suggests tailored professional development, collaboration with computing units, and clear AI policies. Though region- and interview-based, findings indicate prompt engineering can become a key pedagogical and methodological skill in universities. Copyright © 2026, IGI Global Scientific Publishing. Copying or distributing in print or electronic forms without written permission of IGI Global Scientific Publishing is prohibited. Use of this chapter to train generative artificial intelligence (AI) technologies is expressly prohibited. The publisher reserves all rights to license its use for generative AI training and machine learning model development.
Keywords: Electronic Publishing; Ethical Aspects; Learning Systems; Machine Learning; Personnel; Personnel Training; Teaching; Critical Thinking; Design Assessments; Design Thinking; Five State; High Educations; Interpretivist; Materials Design; Student-Centred; Supported Materials; Thematic Analysis; Engineering Education